2022
DOI: 10.1007/s10620-022-07687-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hepatitis B Virus Infection on Patients with COVID-19: A Meta-Analysis

Abstract: Background The COVID-19 pandemic has brought new problems to patients infected with hepatitis B virus (HBV). Aim We aim to know the effects of HBV infection on patients with COVID-19. Methods We searched PubMed, Embase, and Web of Science for data and utilized Stata 14.0 software for this meta-analysis with a random-effects model. This paper was conducted in alignment with the preferred reporting items for systematic review and meta-analysis (PRISMA) guideline. Results In total, 37,696 patients were divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 63 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…Limited data on SARS-CoV-2 infections in patients with chronic HBV and HCV infection show conflicting results. For example, in HBV/SARS-CoV-2 co-infected patients, some studies have reported a higher severity and mortality of COVID-19 compared with the general population,63 64 while this has not been observed by others 65 66. Similarly, in HCV/SARS-CoV-2 co-infection, some reports have indicated a similar COVID-19 outcome compared with healthy individuals,67 while others have shown a higher SARS-CoV-2-associated mortality in HCV-infected patients 68…”
Section: Sars-cov-2 and Clinical Impact On Cldmentioning
confidence: 97%
“…Limited data on SARS-CoV-2 infections in patients with chronic HBV and HCV infection show conflicting results. For example, in HBV/SARS-CoV-2 co-infected patients, some studies have reported a higher severity and mortality of COVID-19 compared with the general population,63 64 while this has not been observed by others 65 66. Similarly, in HCV/SARS-CoV-2 co-infection, some reports have indicated a similar COVID-19 outcome compared with healthy individuals,67 while others have shown a higher SARS-CoV-2-associated mortality in HCV-infected patients 68…”
Section: Sars-cov-2 and Clinical Impact On Cldmentioning
confidence: 97%
“…Sepsis is one of the most common serious complications caused by infectious diseases, which is a very important public health problem with a high fatality rate [17, 21]. Previous studies have shown that coinfection of hepatitis B patients with other viruses may be associated with poorer clinical course [10, 15, 22]. It is not clear whether there is a possibility of worse outcomes after sepsis in patients with hepatitis B infection.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis B is a major global public health problem, and despite impressive progress in preventing chronic infections and reducing mortality, hepatitis B virus (HBV) infection remains a leading cause of premature death [6]. Chronic HBV infection was prone to coinfection with pathogens including bacteria and viruses [7][8][9][10]. In disease states of chronic viral infection, persistent T-cell receptors and inflammatory signalling drive CD8 + T cells into a state of dysfunction, leading to CD8 + T-cell depletion [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies that have examined the influence of HBV on COVID-19 prognosis have been conducted in China due to the high prevalence of HBV in the country[ 60 ]. Yu et al [ 61 ] reported higher in-hospital mortality, more severe disease, and liver function abnormalities in COVID-19 patients infected with HBV compared to COVID-19 patients without HBV. However, the presence of COVID-19 infection or treatment with tocilizumab or corticosteroids could reactivate hepatitis B infection[ 49 , 62 ].…”
Section: Covid-19 In Patients With Pre-existing Liver Diseasementioning
confidence: 99%